Parental nutritional programming and a reminder during juvenile stage affect growth, lipid metabolism and utilisation in later developmental stages of a marine teleost, the gilthead sea bream (Sparus aurata). Issue 7 (10th February 2017) - Turkmen, Serhat; Zamorano, Maria J.; Fernández-Palacios, Hipólito; Hernández-Cruz, Carmen M.; Montero, Daniel; Robaina, Lidia; Izquierdo, Marisol
Abstract: Nutrition during periconception and early development can modulate metabolic routes to prepare the offspring for adverse conditions through a process known as nutritional programming. In gilthead sea bream, replacement of fish oil (FO) with linseed oil (LO) in broodstock diets improves growth in the 4-month-old offspring challenged with low-FO and low-fishmeal (FM) diets for 1 month. The present study further investigated the effects of broodstock feeding on the same offspring when they were 16 months old and were challenged for a second time with the low-FM and low-FO diet for 2 months. The results showed that replacement of parental moderate-FO feeding with LO, combined with juvenile feeding at 4 months old with low-FM and low-FO diets, significantly ( P <0·05) improved offspring growth and feed utilisation of low-FM/FO diets even when they were 16 months old: that is, when they were on the verge of their first reproductive season. Liver fatty acid composition was significantly affected by broodstock or reminder diets as well as by their interaction. Moreover, the reduction of long-chain PUFA and increase in α -linolenic acid and linoleic acid in broodstock diets lead to a significant down-regulation of hepatic lipoprotein lipase ( P <0·001) and elongation of very long-chain fatty acids protein 6 ( P <0·01). Besides, fatty acid desaturase 2 values were positively correlated to hepatic levels of 18 : 4 n -3, 18 : 3 n -6, 20 : 5 n -3, 22 : 6 n -3 and 22 : 5 n -6. Thus, this study demonstrated the long-term nutritional programming of gilthead sea bream through broodstock feeding, the effect of feeding a 'reminder' diet during juvenile stages to improve utilisation of low-FM/FO diets and fish growth as well as the regulation of gene expression along the fish's life-cycle.